2004
DOI: 10.1158/0008-5472.can-03-2630
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Radiation-Induced Cell Killing and Prolongation of γH2AX Foci Expression by the Histone Deacetylase Inhibitor MS-275

Abstract: Histone deacetylase (HDAC) inhibitors are undergoing clinical evaluation for cancer therapy. Because HDAC modulates chromatin structure and gene expression, parameters considered to influence radioresponse, we have investigated the effects of the HDAC inhibitor MS-275 on the radiosensitivity of two human tumor cell lines (DU145 prostate carcinoma and U251 glioma). Acetylation status of histones H3 and H4 was determined as a function of time after MS-275 addition to and removal from culture medium. Histone acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
172
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(181 citation statements)
references
References 23 publications
8
172
0
1
Order By: Relevance
“…In contrast, there has been a lack of studies investigating the role of FLIP in regulating IR-induced apoptosis, possibly because early studies in Jurkat cells reported that FLIP was unable to prevent IR-induced apoptosis in this model (37). While some studies have unsurprisingly shown that FLIP regulates apoptosis in response to combined treatment with IR and TRAIL HDAC inhibitors such as vorinostat and entinostat prevent the deacetylation of histone and non-histone proteins and have been shown to sensitise cancer cells to chemotherapy and IR (41)(42)(43). In this study, we demonstrate that HDAC inhibitors enhance the in vitro and in vivo efficacy of IR in NSCLC models.…”
Section: Discussionmentioning
confidence: 51%
“…In contrast, there has been a lack of studies investigating the role of FLIP in regulating IR-induced apoptosis, possibly because early studies in Jurkat cells reported that FLIP was unable to prevent IR-induced apoptosis in this model (37). While some studies have unsurprisingly shown that FLIP regulates apoptosis in response to combined treatment with IR and TRAIL HDAC inhibitors such as vorinostat and entinostat prevent the deacetylation of histone and non-histone proteins and have been shown to sensitise cancer cells to chemotherapy and IR (41)(42)(43). In this study, we demonstrate that HDAC inhibitors enhance the in vitro and in vivo efficacy of IR in NSCLC models.…”
Section: Discussionmentioning
confidence: 51%
“…It is established that the g-H2AX form of the histone has an important role in recruiting repair factors to nuclear foci following induction of DSBs (Paull et al, 2000;Celeste et al, 2003;Olive and Banath, 2004). Recent studies have shown that incubation of cells with HDAC inhibitors including MS-275 and sodium butyrate, results in prolonged expression of induced g-H2AX foci (Camphausen et al, 2004a;Munshi et al, 2005). These findings indicate that HDAC inhibitor-mediated radiosensitization is associated with a decrease in the repair of DSBs.…”
Section: Mechanisms Of Hdac Inhibitor-mediated Enhanced Radiation Senmentioning
confidence: 96%
“…In fact, HDACi can inhibit DNA repair responses in a few cell lines, which might increase the sensitivity of tumour cells to chemotherapy and radiotherapy by leading to increased DNA damage by these treatments 85,86 .…”
Section: The Cellular Effects Of Hdacimentioning
confidence: 99%